Conserved alternative and antisense transcripts at the programmed cell death 2 locus - Mihola, Ondrej; Forejt, Jiri; Trachtulec, Zdenek (BMC genomics, 2007)
BACKGROUND: The programmed cell death 2 (Pdcd2) gene on mouse chromosome 17 was evaluated as a member of a highly conserved synteny, a candidate for an imprinted locus, and a candidate for the Hybrid sterility 1 (Hst1) gene. RESULTS: New mouse transcripts were identified at this locus: an alternative Pdcd2 mRNA skipping the last two coding exons and two classes of antisense RNAs. One class of the antisense RNA overlaps the alternative exon and the other the entire Pdcd2 gene. The antisense RNAs are alternative transcripts of the neighboring TATA-binding protein gene (Tbp) that are located mainly in the cell nucleus. Analogous alternative PDCD2 forms truncating the C-terminal domain were also detected in human and chicken. Alternative transcripts of the chicken PDCD2 and TBP genes also overlap. No correlation in the transcription of the alternative and overlapping mRNAs was detected. Allelic sequencing and transcription studies did not reveal any support for the candidacy of Pdcd2 for Hst1. No correlated expression of Pdcd2 with the other two genes of the highly conserved synteny was observed. Pdcd2, Chd1, and four other genes from this region were not imprinted in the embryo. CONCLUSION: The conservation of alternative transcription of the Pdcd2 gene in mouse, human and chicken suggests the biological importance of such truncated protein. The biological function of the alternative PDCD2 is likely to be opposite to that of the constitutive form. The ratio of the constitutive and alternative Pdcd2 mRNAs differs in the tissues, suggesting a developmental role. The identified Tbp-alternative Pdcd2-antisense transcripts may interfere with the transcription of the Pdcd2 gene, as they are transcribed at a comparable level. The conservation of the Pdcd2/Tbp sense-antisense overlap in the mouse and chicken points out its biological relevance. Our results also suggest that some cDNAs in databases labeled as noncoding are incomplete alternative cDNAs of neighboring protein-coding genes.
Keywords: polymerázová řetězová reakce; apoptóza; exprimované sekvenční adresy; genomový imprinting; mapování chromozomů; lidé; kur domácí; Chickens; Apoptosis; Genomic Imprinting; proteiny regulující apoptózu; krysa rodu Rattus; messenger RNA; RNA, Messenger; myši; Humans; Polymerase Chain Reaction; Mice; Alternative Splicing; mužské pohlaví; Expressed Sequence Tags; alternativní sestřih; zvířata; Chromosome Mapping; Alleles; Rats; Animals; molekulární sekvence - údaje; Apoptosis Regulatory Proteins; Male; alely; Molecular Sequence Data